(untitled) (ENTHYMEMA, 2017)
Sull’aporia che emerge dalle Tesi di Praga fra approccio intrinseco e approccio estrinseco ai fatti linguistici e letterari. Sul significato del primo e del secondo nella critica e nella teoria letteraria del Novecento e del presente. On the aporia emerging from the Prague Theses between intrinsic approach and extrinsic approach to the linguistic and literary facts. On the meaning of both approaches in literary criticism and literary theory of the twentieth century and of the present.